K-Pop Fandom Activism on Social Media: Refuting Accusations of Slacktivism in Internet Activism - Saka, Putri Ananda; Saka, Zidan Abdul Jabar; Nurhakim, Putri Rahmah; Yusuf, Mirna; Larasati, Yuniar Galuh; Adawiah, Rabiatul (Fenomena, 2024)
The phenomenon of K-Pop fandom activism, which has been considered as a mere fanaticism movement, has experienced a developmental orientation towards the fulfillment of common interests. K-Pop fandom activism is able to become a movement in social media that has an impact and brings public attention in voicing social changes. This paper focuses on analyzing the trends, forms, and real implications of social movements initiated by K-Pop fandoms with a high number of masses and militants. Using qualitative research utilizing online sources, this study found that K-Pop fandom activism has enlivened issues that are not only related to their community but have referred to global issues such as social, cultural, environmental and political. This activism is able to become a catalyst on social media in the form of real action rather than slacktivism. Real action is carried out by giving donations, filling out petitions to make demonstration efforts. This activism phenomenon has implications for changes not only in the issues raised but also has implications for changes in the stigma of society towards K-Pop fandom which tends to be more positive as a driver of social change. However, this paper is limited to the use of text data as the main source which cannot provide empirical conclusions. Therefore, future research should integrate the views and experiences of those directly involved in K-Pop fandom activism so that it is possible to formulate more comprehensive conclusions. Fenomena aktivisme fandom K-Pop yang selama ini dianggap sebagai gerakan fanatisme belaka ternyata telah mengalami perkembangan orientasi atas pemenuhan kepentingan bersama. Aktivisme fandom K-Pop mampu menjadi gerakan dalam media sosial yang berdampak dan membawa atensi publik dalam menyuarakan perubahan-perubahan sosial. Tulisan ini fokus menganalisis tren, bentuk, dan implikasi nyata dari gerakan sosial yang diinisiasi oleh fandom K-Pop dengan jumlah massa yang cukup tinggi dan militan. Menggunakan penelitian kualitatif dengan memanfaatkan sumber-sumber online, penelitian ini menemukan bahwa aktivisme fandom K-Pop sudah meramaikan isu-isu yang bukan hanya terkait komunitas mereka saja melainkan sudah merujuk pada isu-isu global seperti sosial, kultural, lingkungan hingga politik. Aktivisme ini mampu menjadi katalis di media sosial berupa aksi nyata bukan sebagai slacktivisme. Aksi nyata yang dilakukan dengan pemberian donasi, mengisi petisi hingga melakukan upaya demonstrasi. Fenomena aktivisme ini berimplikasi pada perubahan tidak hanya pada isu yang diangkat melainkan juga berimplikasi pada perubahan stigma masyarakat terhadap fandom K-Pop yang cendrung lebih positif sebagai penggerak perubahan sosial. Akan tetapi, tulisan ini terbatas pada penggunaan data teks yang menjadi sumber utama yang tidak dapat memberikan kesimpulan empiris. Oleh karena itu, penelitian masa depan harus mengintegrasikan pandangan dan pengalaman pihak yang terlibat langsung dalam aktivisme fandom K-Pop sehingga memungkinkan untuk merumuskan kesimpulan yang lebih komprehensif.